Cultura de segurança do paciente em serviços de atenção obstétrica - Juliana Maria Almeida do Carmo (2018)
The Culture of Patient Safety is considered an important structural component of health services, which favors the implementation of safe practices for the reduction of adverse events. Knowingthesafetyculturethroughvalidatedquestionnairesallowsananalysisofthedimensions involvedinthecareofhealthorganizationsandidentiesopportunitiesforimprovementinsafety. Overall objective: to analyze the safety culture of the patient in obstetric care services, from the perspective of the multiprofessional team. Method: This is a descriptive, cross-sectional study with a quantitative approach. The questionnaire Hospital Survey on Patient Safety Culture was used as instrument of data collection. The sample consisted of 301 health professionals from the multidisciplinary team of three obstetric care services in the city of Belo Horizonte. Data were analyzed according to the Mann-Whitney and Kruskal-Wallis tests. Spearmans correlation was also used to verify the association between the dimensions and the characterizing variables. Results: the majority of the professionals were from obstetrics 70%, the working time in the area and in the hospital that predominated was one to ve years; 40% of professionals work from 40 to 59 hours, 27% are nurses; 96% provide direct patient care. It was identied that all the dimensions obtained percentages below 75%. Only the dimensions Organizational learning and continuous improvement; Expectations and actions of the supervisor \ boss for patient safety and; Teamwork within the unit obtained percentages equal to or above 50%. On the other hand, General perception of patient safety, Frequency of reported events and Non-punitive response to error were the dimensions with the lowest index of positive responses. Conclusion: no strength areas were identied in the dimensions evaluated by the Survey on Patient Safety Culture questionnaire, in the three obstetric care services. Strategies for patient safety culture need to be developed for health professionals to identify safe attitudes and behaviors in obstetric care